Investigating the Horizontal Mathematization Process for Students with Diverse Adversity Quotients in Solving PISA-Oriented Problems - Hanifah, Whikan Ayu; Triyanto, Triyanto; Fitriana, Laila (FKIP Universitas Lampung, 2024)
Investigating the Horizontal Mathematization Process for Students with Diverse Adversity Quotients in Solving PISA-Oriented Problems. Objectives: This study aims to understand the horizontal mathematization process of students with climber, camper, and quitter types of Adversity Quotient (AQ) in solving PISA-oriented problems. Methods: This research employs a qualitative approach. Data was collected using questionnaires, written tests, and unstructured interviews. The data was analyzed through data reduction, presentation, and verification or conclusion. Findings: The research results indicate that students of SMP Negeri 9 Surakarta in the 2023/2024 academic year with a climber AQ type have already developed the ability to solve PISA-oriented problems using the horizontal mathematization process well. Students with a camper AQ type have already developed the ability to solve PISA-oriented problems reasonably using the horizontal mathematization process. Meanwhile, students with a quitter AQ type have not yet developed the ability to solve PISA-oriented problems using the horizontal mathematization process. Conclusion: Based on this research, students with a climber AQ type have a better or higher mathematical process than those with a camper or quitter AQ type. Keywords: adversity quotient, horizontal mathematization process, PISA.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024115